104 Impact of diagnostic advices in cancer care in Aquitaine. (23rd September 2015) - Lapeyrere, Nadege; Parrens, Marie; Coindre, Jean Michel; Soubeyran, Isabelle; De Mascarel, Antoine; Philippe, Merlio Jean; Le Bail, Brigitte; Lepreux, Sébastien; Mathoulin-Pélissier, Simone; Vergier, Béatrice
Abstract : Context, objectives: Treatments and prognosis for patients with cancers are most often based on histological and/or cytological diagnoses performed by pathologists. Errors are probably the most harmful and expensive types of diagnostic errors, especially for cancer, so an expert second opinion on lesions which are difficult to analyse can be particularly valuable for pathologists (and patients). Such expert review can lead to confirmation or revision of the initial diagnosis and greatly impact the therapeutic management and prognosis of patients. To our knowledge, little is known about the impact of pathology review on patient care. The objective of our study was to focus on the voluntary sending of specimens by pathologists for a second opinion to evaluate its impact on the management of cancer patients in Aquitaine, a region of France. Program: The study was first quantitative performed retrospectively on all cases of cancer, voluntary sent in 2006 by a pathologist located in a French region (Aquitaine) to an expert pathologist for a second opinion. We excluded samples sent only for specific additional analyses or submitted by clinicians. Secondly we restricted the study to lymphoid, melanocytic and soft tissue tumours sent for second opinion in order to analyse their diagnostic, therapeutic and prognostic impact. The initial diagnosis was compared to the expert diagnostic. We considered that the expert review had an important diagnosic impact either when the initial pathologist sent the specimen to identify or classify malignant tumour, or hesitated between benign and malignant tumour or had no hypothesis, or if there were discordant diagnoses (malignant/benign) between the two pathologists. We considered that the expert review had a high therapeutic impact if the disagreement between initial and expert diagnoses induced a complete modification in therapy. Results: Thousand three hundred thirty six out of all 3781 second opinion cases were sent by pathologists in Aquitaine: 751 samples (56%) were submitted for lymphoid (55%), melanocytic (15%) or soft tissues tumours (30%). There was an important diagnostic impact for 75% of the sample since the expert pathologists identified or classified malignant tumours (60%), made a diagnosis different from the initial diagnosis (9%), or provided a complete diagnosis (6%). The impact of the expert review on patient management was considered high for 46% of specimens (50% for lymphoid, 44% for melanocytic and 39% for soft tissue tumour), resulting in clinically relevant changes. Among the 706 specimens for which there was an initial diagnosis, the expert diagnosis modified the clinical prognosis in 40% of the specimens (similar proportions for better or worse prognosis). Discussion and conclusion: This study emphasises the importance of expert pathological second opinion in cancer pathology. But, our study is interested only on lymphoid, melanocytic and soft tissue tumours, samples more complex than others tumours. So, the question remains regarding which slides should be reviewed. Nevertheless, a high therapeutic impact justifies the needs for a second opinion in problematic cases because a correct diagnosis with adapted treatment is preferable to a false diagnosis with inappropriate management. Contexte, objectif: La prise en charge et le pronostic de patients atteints de cancer sont déterminés par le diagnostic histologique et/ou cytologique établis par les pathologistes. Les erreurs diagnostiques sont certainement les plus dangereuses et les plus couteuses, notamment dans le domaine du cancer; une expertise des lésions les plus difficiles à analyser doit être valorisée pour les pathologistes. Ainsi, des relectures par des experts peuvent être effectuées pour confirmer ou préciser le diagnostic initial ce qui peut avoir un impact sur la prise en charge du patient. Toutefois, dans la littérature, nous retrouvons peu d'études menées sur l'impact d'un second avis. L'objectif de cette étude était d'évaluer l'impact thérapeutique des avis en cancérologie donnés en Aquitaine. Programme: Une étude quantitative rétrospective a été effectuée sur tous les avis et relectures, envoyés volontairement en 2006 par un pathologiste de la région Aquitaine à un expert référent. Ont été exclus les relectures demandées par un clinicien et les avis adressés uniquement à but technique. Un échantillon des avis régionaux adressés pour tumeurs lymphoïdes, mélaniques et conjonctives a été sélectionné afin d'analyser l'impact diagnostique, thérapeutique et pronostique. La proposition diagnostique du pathologiste initial a été comparée au diagnostic du pathologiste expert. L'impact diagnostique était déterminé majeur lorsque l'avis était envoyé pour tumeur maligne à typer ou à identifier, doute bénin/malin, diagnostic non précisé ou si les diagnostics étaient discordants (malin/bénin). L'impact thérapeutique était jugé fort si l'avis engendrait une modification radicale du traitement. Résultats: Sur 3781 avis reçus, 1336 étaient envoyés par un pathologiste aquitain (75%); 751 (56%) correspondaient à des tumeurs lymphoïdes (55%), conjonctives (30%) et mélaniques (15%). L'avis donné par l'expert a induit un impact diagnostique majeur dans 75% des cas regroupant 60% de tumeur maligne à typer ou à classer, 9% de discordance majeure bénin/malin et 6% de diagnostic initial non précisé. L'avis donné par l'expert a eu un impact thérapeutique fort dans 46% des cas (50% pour les tumeurs lymphoïdes, 44% pour les mélaniques et 39% pour les tumeurs conjonctives) résultant à une modification « radicale » du traitement suite à cet avis. Parmi les 706 cas pour lesquels il y avait un diagnostic initial précisé, l'avis de l'expert a modifié le pronostic clinique pour 40% d'entre eux (cet impact est meilleur pour la moitié de ces avis). Discussion et Conclusion: Cette étude souligne l'importance des avis diagnostiques dans le domaine de la cancérologie. Mais cette étude s'est intéressée uniquement aux avis envoyés pour tumeurs lymphoïdes, mélaniques et conjonctives, qui sont des tumeurs complexes. Une question reste donc en suspend concernant les cas qui doivent être envoyés pour second avis. Toutefois, un fort impact thérapeutique justifie la nécessité de demander un second avis pour des cas problématiques car un diagnostic correct avec un traitement adapté est préférable à un diagnostic erroné qui amène à une prise en charge inappropriée.